2022
DOI: 10.3389/fendo.2022.975647
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and sarcopenia-related traits: A bi-directional Mendelian randomization study

Abstract: BackgroundWith the advancement of world population aging, age-related osteoporosis (OP) and sarcopenia (SP) impose enormous clinical and economic burden on society. Evidence from accumulating studies indicates that they mutually influence one another. However, an observational study may be affected by potential confounders. Meanwhile, a Mendelian randomization (MR) study can overcome these confounders to assess causality.ObjectivesThe aim of this study was to evaluate the causality between OP and SP, informing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Much research has focused on the relationships between body composition and BMD. Briefly, muscle mass, strength, and bone density have generally been found to correlate positively across groups 4,[60][61][62][63][64][65][66] likely sharing a causal relationship [67][68][69] , while the association between adiposity and BMD is more complex with some evidence of positive correlations between adiposity and the BMD of weight-bearing bones 64,66,67,70,71 that may attenuate or even reverse after accounting for adiposity type 65,[72][73][74] , at extreme ranges of adiposity 66,74,75 , or in certain age and sex-based subpopulations 64,67,73,76 . The complexity of these prior results coincides well with our observation of effect direction heterogeneity across signals fine-mapped for both body-composition traits and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has focused on the relationships between body composition and BMD. Briefly, muscle mass, strength, and bone density have generally been found to correlate positively across groups 4,[60][61][62][63][64][65][66] likely sharing a causal relationship [67][68][69] , while the association between adiposity and BMD is more complex with some evidence of positive correlations between adiposity and the BMD of weight-bearing bones 64,66,67,70,71 that may attenuate or even reverse after accounting for adiposity type 65,[72][73][74] , at extreme ranges of adiposity 66,74,75 , or in certain age and sex-based subpopulations 64,67,73,76 . The complexity of these prior results coincides well with our observation of effect direction heterogeneity across signals fine-mapped for both body-composition traits and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…If there was horizontal pleiotropy, the MR-Egger estimation would be the main effect size. 34 In this study, we used Two Sample MR packages (version 0.5.6) to perform the MR analysis in R (version 4.2.1). The statistical significance level was set at p < .05.…”
Section: Methodsmentioning
confidence: 99%
“…Others have linked sarcopenia to elevated inflammatory markers as predictors of CVD 6 . Two Mendelian randomization studies utilizing the UK Biobank and other datasets also found individual components of sarcopenia, such as low appendicular lean mass (ALM) and handgrip strength (HGS), to be independent causal risk factors for coronary artery disease and myocardial infarction (MI), though findings were less consistent for stroke 7,8 . Despite the associations with surrogate markers and the intuitive pathophysiology, studies on the direct association of sarcopenia with cardiovascular events have shown mixed results.…”
Section: Figurementioning
confidence: 99%
“…6 Two Mendelian randomization studies utilizing the UK Biobank and other datasets also found individual components of sarcopenia, such as low appendicular lean mass (ALM) and handgrip strength (HGS), to be independent causal risk factors for coronary artery disease and myocardial infarction (MI), though findings were less consistent for stroke. 7,8 Despite the associations with surrogate markers and the intuitive pathophysiology, studies on the direct association of sarcopenia with cardiovascular events have shown mixed results. For example, a 2020 UK Biobank study found sarcopenia, defined by low muscle mass and strength using the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) criteria, not to be associated with incident CVD (MI or stroke).…”
mentioning
confidence: 99%